PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH MENGGUNAKAN PEMBELAJARAN DIFERENSIASI UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS VII B SMP NEGERI 19 PALU PADA MATERI VOLUME DAN LUAS PERMUKAAN KUBUS SERTA BALOK - Wini Wini; Muh. Rizal; Nurhayadi Nurhayadi; Mubarik Mubarik (Universitas Tadulako, 2025)
The problem in this research is that one of the mathematical materials that is considered difficult by students is the material on flat-sided solid shapes of cubes and cuboids. One of the causes of the lowstudent learning outcomes due to lack of student interest in mathematics lessons, students are not active in learning, students only tend to memorize not understanding the concept and lack of interaction between students and teachers so that students often make mistakes in solving problems, mistakes shown by students in mathematics learning are not only caused by this subject has an abstract nature and requires a serious learning atmosphere, but also influenced by factors from the students themselves and their environment. This type of research is Classroom Action Research (CAR). Data collection techniques in this study used observation, interviews and field notes. This study consists of two stages, namely the pre-action stage and the implementation of the action. The results of this study indicate that the application of a problem-based learning model using differentiated learning can improve student learning outcomes in the material on the volume and surface area of ​​cubes and cuboids through the following stages: (1) orienting students to the problem, the teacher presents the material, (2) organizing students to learn, the teacher forms study groups, (3) guiding individual and group investigations, the teacher guides students in collecting information, (4) developing and presenting the results of their work, the teacher asks several groups to present the results of their discussions to their friends in front of the class, and (5) analyzing and evaluating the problem-solving process, the teacher and students together conclude the material that has been studied.